2019
DOI: 10.3390/ijms20071641
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate in Endothelial Cell Recellularization Improves Patency and Endothelialization of Decellularized Vascular Grafts In Vivo

Abstract: Background: S1P has been shown to improve the endothelialization of decellularized vascular grafts in vitro. Here, we evaluated the potential of tissue-engineered vascular grafts (TEVGs) constructed by ECs and S1P on decellularized vascular scaffolds in a rat model. Methods: Rat aorta was decellularized mainly by 0.1% SDS and characterized by histology. Rat ECs, were seeded onto decellularized scaffolds, and the viability of the ECs was evaluated by biochemical assays. Then, we investigated the in vivo patency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Various vessels have been decellularized in order to obtain a vascular graft, as for example, the carotid artery ( 30 ), aorta artery ( 32 , 60 ), internal mammary artery ( 61 ), umbilical artery ( 62 ), saphenous vein ( 63 ), coronary artery ( 64 ), femoral vein ( 58 ), and the vena cava ( 55 ). The protocols for vessel decellularization include a number of agents, such as surfactants, enzymes, solvents, and physical methods.…”
Section: Vte Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various vessels have been decellularized in order to obtain a vascular graft, as for example, the carotid artery ( 30 ), aorta artery ( 32 , 60 ), internal mammary artery ( 61 ), umbilical artery ( 62 ), saphenous vein ( 63 ), coronary artery ( 64 ), femoral vein ( 58 ), and the vena cava ( 55 ). The protocols for vessel decellularization include a number of agents, such as surfactants, enzymes, solvents, and physical methods.…”
Section: Vte Techniquesmentioning
confidence: 99%
“…Some studies also combine physical methods for chemical or biological agents in order to increase the penetration of agents and increase the decellularization of vascular tissue ( 32 , 55 , 60 , 61 ). Simsa and colleagues evaluated the decellularization of vena cavas with TritonX-100, TnBP, and DNase under static, agitation, and perfusion conditions.…”
Section: Vte Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the 14-day follow-up, only one of six rats was alive in the non-endothelialization group, the vascular grafts were short of ECs and there was endothelial damage and thrombotic plaque formation on the luminal side. In contrast, four of six rats were alive in the re-endothelialization groups, ECs are observed in the implanted vascular grafts and there were fewer thrombotic plaques or fibrin clots that were noted in the lumen [ 83 ]. Besides, compared with the control group, the decellularized vessels of re-endothelialization in vitro retained >95% monolayer EC coverage in 1 h after implantation, endothelial coverage increased.…”
Section: Selection Of Endothelialization Forms For Tevgs With Differementioning
confidence: 99%
“…In our previous work, we found that using S1P to enhance EC attachment in a tissue-engineered vascular scaffold and the S1P-augmented endothelium significantly enhanced antithrombotic surface properties due to reduced syndecan-1 (SDC-1) shedding [25]. Furthermore, we demonstrated that S1P enhances the patency of EC-recellularized vascular scaffolds in a rat aorta implantation model [26]. The main point of S1P on EC that could prevent platelet adhesion because it promotes SDC-1 expression and prevents SDC-1 shedding.…”
Section: Introductionmentioning
confidence: 99%